KONTRADIKSI ANTI TAKWIL âABDUL âAZÃZ BIN âABDULLÃH BIN BÃZ: TAFSIR TERHADAP ANTROPOMORPHISME - Mujahid, Ahmad (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2015)
In Qurâanic studies, the issues of Muhkam and Mutasyabbih verses always have been discussed, how to understandÂ each them. Interpreting mutasyabihat verses has been a need because many of them tell about theology in the context ofÂ anthropomorphism. Almost all scholars tend to use takwil to interpret them, but Abdul Azîz bin Abdullâh bin BÃ¢zÂ offered the opposite method. He avoided takwil. In this study, this writing discusses how Ibn Bâz understood mutasyabihatÂ verses especially about anthropomorphism. As a conclusion, the researcher found that the anti-takwil is stated by IbnÂ Bâz and his allies, in its practice was sometimes contradictory. To enrich this article, the writer will trace the genealogyÂ of the thought of Ibn Bâz and his dialectic with the understanding or other streams such as Muâtazilah, AsyâariyyahÂ to MaturidiyahÂ